[Saunders, Christopher (singer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Christopher Saunders is an Australian tenor. He performs in opera and operetta as well as oratorio, lieder and song. A graduate of the Guildhall School of Music and Drama in London, he studied with Vera Roza, and was a Samling Scholar studying with Sir Thomas Allen and Malcolm Martineau.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Saunders, Christopher -- Miscellanea; Tenors (Singers) -- Australia -- Miscellanea; Singers -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian